Current Strategy for Cisplatin Delivery - Yue, Zhanguo; Cao, Zhiqiang (Current Cancer Drug Targets, 2016)
Cisplatin is one of the leading chemotherapy drugs currently used in clinical settings. However, its serious side effects and its resistance developed by tumor cells hinder its usage. To decrease its side effects and maintain anti-cancer efficiency, various cisplatin based formulations were developed. In this minireview, we summarized the recent progress of cisplatin delivery strategies, including direct delivery, prodrug delivery and combination delivery. Key challenges preventing the development of improved drug formulations were identified, and effective approaches to address these issues were discussed in the context of these recent works.
Keywords: Cisplatin